2014
DOI: 10.1101/lm.035089.114
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive context conditioning proactively, but transiently, interferes with expression of counterconditioned context fear

Abstract: Four experiments used rats to study appetitive-aversive transfer. Rats trained to eat a palatable food in a distinctive context and shocked in that context ate and did not freeze when tested 1 d later but froze and did not eat when tested 14 d later. These results were associatively mediated (Experiments 1 and 2), observed when rats were or were not food deprived (Experiments 1 and 2), and were not due to latent inhibition (Experiment 3). In contrast, rats trained to eat in the context and shocked there 13 d l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Rats were tested twice, once in the aversive context and once in the appetitive context. As expected McNally, 2012, 2013;Holmes and Westbrook, 2014), rats expressed appetitive (i.e., magazine entries) and aversive (i.e., freezing) behavior in both contexts (Fig. 1E).…”
Section: Testsupporting
confidence: 84%
See 1 more Smart Citation
“…Rats were tested twice, once in the aversive context and once in the appetitive context. As expected McNally, 2012, 2013;Holmes and Westbrook, 2014), rats expressed appetitive (i.e., magazine entries) and aversive (i.e., freezing) behavior in both contexts (Fig. 1E).…”
Section: Testsupporting
confidence: 84%
“…Here we studied motivational conflict using Pavlovian counterconditioning (Dickinson and Pearce, 1977;Lovibond and Dickinson, 1982;McNally, 2012, 2013;Holmes and Westbrook, 2014). In counterconditioning, a conditioned stimulus (CS) from one motivational class is transformed into a CS of a contrasting motivational class (e.g., signal for reward is transformed into a signal for danger).…”
Section: Introductionmentioning
confidence: 99%
“…There are many possibilities for this, including consolidation of the prediction error that occurred in extinction (Abraham et al, 2014), a D1-mediated prolonged window of inhibitory memory activity (Wagner, 1981), or counterconditioning of aversive fear memory by the rewarding properties of SKF81297 (Holmes and Westbrook, 2014). Our findings that SKF81297 induced a CPP when it was used as the US suggest that counterconditioning is a possibility for the enhanced fear extinction effects, and previous studies have shown that fear learning is subject to opponent interactions between appetitive and aversive processes (Nasser and McNally, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, this dominance is hardly universal. Other motivational states can trump fear (Burnett et al, 2016;Choi et al, 2019;Choi and McNally, 2017;Holmes and Westbrook, 2014). At some point, the hungry animal is willing to tolerate and then overcome adversity and fear to meet its metabolic need (Burnett et al, 2019;Burnett et al, 2016;Choi et al, 2019;Choi and McNally, 2017;Miller, 1960) just as a sick parent interrupts its own recuperation to care for its young (Aubert, 1999).…”
Section: Behavior Systemsmentioning
confidence: 99%